α-Synuclein oligomers impair neuronal microtubule-kinesin interplay. - Winner, Beate; Prots, Iryna; Brey, Stefanie; et al. (Journal of Biological Chemistry, 2013)
Early α-synuclein (α-Syn)-induced alterations are neurite pathologies resulting in Lewy neurites. α-Syn oligomers are a toxic species in synucleinopathies and are suspected to cause neuritic pathology. To investigate how α-Syn oligomers may be linked to aberrant neurite pathology, we modeled different stages of α-Syn aggregation in vitro and investigated the interplay of α-Syn aggregates with proteins involved in axonal transport. The interaction of wild type α-Syn (WTS) and α-Syn variants (E57K, A30P, and aSyn(30-110)) with kinesin, tubulin, and the microtubule (MT)-associated proteins, MAP2 and Tau, is stronger for multimers than for monomers. WTS seeds but not α-Syn oligomers significantly and dose-dependently reduced Tau-promoted MT assembly in vitro. In contrast, MT gliding velocity across kinesin-coated surfaces was significantly decreased in the presence of α-Syn oligomers but not WTS seeds or fibrils (aSyn(30-110) multimers). In a human dopaminergic neuronal cell line, mild overexpression of the oligomerizing E57K α-Syn variant significantly impaired neurite network morphology without causing profound cell death. In accordance with these findings, MT stability, neuritic kinesin, and neuritic kinesin-dependent cargoes were significantly reduced by the presence of α-Syn oligomers. In summary, different α-Syn species act divergently on the axonal transport machinery. These findings provide new insights into α-Syn oligomer-driven neuritic pathology as one of the earliest events in synucleinopathies.